CENOZOIC EXHUMATION AND DEFORMATION OF NORTHEASTERN TIBET AND THE QINLING: IS TIBETAN LOWER CRUSTAL FLOW DIVERGING AROUND THE SICHUAN BASIN? - Enkelmann E.; Ratschbacher L.; Jonckheere R.; Nestler R.; Fleischer M.; Gloaguen R.; Hacker B.R.; Zhang Y.Q.; Ma Y.-S. (My University, 2006)
Apatite fission-track thermochronology data elucidate the cooling/ exhumation history of the Qinling (Qin Mountains), which contain a Paleozoic-Mesozoic orogenic collage north of the Sichuan Basin and northeast of the Tibetan Plateau. In particular, we examine the extent to which the Qinling were affected by the rising plateau. The northern and eastern Qinling show continuous cooling and slow exhumation since the Cretaceous. In contrast, in the southwestern Qinling, rapid cooling initiated at 9-4 Ma, a few million years later than in the eastern Tibetan Plateau. A compilation of major Cenozoic faults in the eastern Tibetan Plateau and the Qinling, and their kinematic and dynamic characterization, shows that deformation in the Qinling has predominantly been strike slip. Active sinistral and dextral strike-slip faults delineate an area of eastward rock flow and bound the area of rapid late Cenozoic cooling outlined by apatite fission-track thermochronology. These data can be interpreted to indicate that lower crustal flow has been diverted around the Longmen Shan and beneath the southwestern Qinling, causing active plateau uplift in this area. Alternatively, northeastern Tibet may be growing eastward faster in the western Qinling than the entire South China Block is extruding to the east. © 2006 Geological Society of America.
Keywords: FISSION TRACK; PLATEAU GROWTH; QINLING; STRUCTURAL GEOLOGY; TIBET; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая